Diplomasi Lingkungan Indonesia Melalui Coral Triangle Intiative: Peluang dan Tantangan - Putri C, Dinda Amalia; Hidayat, Taopik; Fauzan Ramadhan, Muhammad (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2025)
Indonesia, as one of the largest archipelagic countries with abundant marine biodiversity, plays an important role in environmental diplomacy through the Coral Triangle Initiative (CTI-CFF). This initiative involves six countries in the Coral Triangle region to protect and sustainably manage coastal and marine resources. This article analyzes Indonesia's role in environmental diplomacy through the CTI-CFF, including the challenges and opportunities it faces. A descriptive qualitative research method is used to explore the policy and implementation of environmental diplomacy, with secondary data from relevant literature. The results show that Indonesia has taken strategic steps such as the establishment of Marine Protected Areas (MPAs), capacity building of local communities, and strengthening regional collaboration to address threats such as climate change, illegal fishing, and overfishing. However, challenges, such as the effects of climate change and lack of law enforcement against overfishing activities, remain major obstacles. The article also identifies opportunities through the development of a blue economy that integrates the sustainability of marine ecosystems with economic potential. Indonesia's environmental diplomacy in the CTI-CFF demonstrates a commitment to conserving marine biodiversity, supporting the welfare of coastal communities, and maintaining national economic and food security